The beast and the sovereign in 'Circe': human and animal rights in Joyce studies. Issue 2 (1st February 2022) - Ebury, Katherine
ABSTRACT: My article will seek to interpret Bloom's trials and tribulations in the 'Circe' episode through Derrida's insight that 'between sovereign, criminal and beast, [there exists] a sort of obscure and fascinating complicity', as a way of considering consider what Joyce teaches us about the interplay between human and nonhuman rights in the episode and across Ulysses ( B&S, 17). An analysis of these intertwined categories of being in the episode will reveal how 'Circe' emerges from Joyce's earlier work, such as 'Ireland at the Bar' (1907), in exploring how the sensational violence of colonialism violates both human and animal bodies and reflecting Derrida's sense 'that the animal is already political' (B&S, 14-15, my italics). Moving beyond 'Circe', my essay will function as a case study through which we might address the value of contemporary animal studies approaches to the politics of Joyce's Ulysses, often alongside and sometimes in contrast with a tradition of postcolonial modes of thought, ahead of its centenary.